POSITIVE RESULTS OF THE HIDDEN PROGRAM IN THE EDUCATION OF NURSING STUDENTS TAKING INTERNAL MEDICINE COURSE-A CROSS-SECTIONAL STUDY - KISKAÇ , Neşe; RASHİDİ, Mahruk and KARAMAN , Funda (SSD Journal, 2023)
Objective: The aim of the study was to determine the opinions of nursing students who take internal medicine nursing course about the hidden curriculum. Material and Methods: The research was a descriptive and cross-sectional study. The data were collected by survey method with 233 nursing students. Results: The total score of the students’ hidden curriculum evaluation was found to be 158.05±23.12. A statistically significant difference was found between scale total score and gender and how chose nursing profession (p<0.05). Female students and those who chose the nursing profession willingly had higher scale scores. Conclusion: The nursing profession is a profession that requires a strong sense of responsibility, devotion and high moral values. For this reason, nursing education is also greatly affected by the hidden curriculum. The acquisition of positive interpersonal relations and cultural values is so important in the professional identity formation of nursing students. This can only be gained by the students through the hidden curriculum. Hidden curriculum gains are an issue that universities should work on in terms of gaining professional values and ethical principles. It can be suggested that studies should be carried out in terms of the deficiencies identified in line with the qualitative studies to be carried out, especially with students who think negatively about this subject.